Are Phosphorous and Phosphoric Acids Equal Phosphorous Sources for Plant Growth? - Asha M. Brunings; Guodong Liu; Eric H. Simonne; Shouan Zhang; Yuncong Li; Lawrence E. Datnoff (EDIS, 2012)
Phosphorus (P) is one of the 17 elements essential for plant growth and development, and is also a key component in some agrochemicals, such as phosphorous acid. Thus, there are two types of P closely associated with crop production. The similarity of terms such as phosphoric acid and phosphorous acid may create some confusion as to the actual content and efficacy of these products. This revised 7-page fact sheet explains what phosphorous acid is and examines both its fungicidal activity and nutrient value. Written by Asha M. Brunings, Guodong Liu, Eric H. Simonne, Shouan Zhang, Yuncong Li, and Lawrence E. Datnoff, and published by the UF Department of Horticultural Sciences, March 2012.